Invented History, Fabricated Power : the Narrative Shaping of Civilization and Culture - Wood, Barry (Anthem Press, 2020)
Invented History, Fabricated Power begins with an examination of prehistoric beliefs (in spirits, souls, mana, orenda) that provided personal explanation and power through ritual and shamanism among tribal peoples. On this foundation, spiritual power evolved into various kinds of divine sanction for kings and emperors (Sumerian, Egyptian, Greek, Roman, Indian, Chinese and Japanese). As kingships expanded into empires, fictional histories and millennia-long genealogies developed that portrayed imperial superiority and greatness. Supernatural events and miracles were attached to religious founders (Hebrew, Hindu, Buddhist, Christian, Islamic). A unique variation developed in the Roman Church which fabricated papal power through forgeries in the first millennium CE and the later "doctrine of discovery" which authorized European domination and conquest around the world during the Age of Exploration. Elaborate fabrications continued with epic histories and literary cycles from the Persians, Ethiopians, Franks, British, Portuguese, and Iroquois Indians. Both Marxists and Nazis created doctrinal texts which passed for economic or political explanations but were in fact self-aggrandizing narratives that eventually collapsed. The book ends with the idealistic goals of the current liberal democratic way of life, pointing to its limitations as a sustaining narrative, along with numerous problems threatening its viability over the long term